A call to action: The controversy of and rationale for competency-based medical education. (3rd June 2017) - Holmboe, Eric S.; Sherbino, Jonathan; Englander, Robert; Snell, Linda; Frank, Jason R.
Abstract: Although medical education has enjoyed many successes over the last century, there is a recognition that health care is too often unsafe and of poor quality. Errors in diagnosis and treatment, communication breakdowns, poor care coordination, inappropriate use of tests and procedures, and dysfunctional collaboration harm patients and families around the world. These issues reflect on our current model of medical education and raise the question: Are physicians being adequately prepared for twenty-first century practice? Multiple reports have concluded the answer is "no." Concurrent with this concern is an increasing interest in competency-based medical education (CBME) as an approach to help reform medical education. The principles of CBME are grounded in providing better and safer care. As interest in CBME has increased, so have criticisms of the movement. This article summarizes and addresses objections and challenges related to CBME. These can provide valuable feedback to improve CBME implementation and avoid pitfalls. We strongly believe medical education reform should not be reduced to an "either/or" approach, but should blend theories and approaches to suit the needs and resources of the populations served. The incorporation of milestones and entrustable professional activities within existing competency frameworks speaks to the dynamic evolution of CBME, which should not be viewed as a fixed doctrine, but rather as a set of evolving concepts, principles, tools, and approaches that can enable important reforms in medical education that, in turn, enable the best outcomes for patients.